High growth recovery ability of Eucalyptus grandis trees following a 3-year period of 80% throughfall reduction - Chambi-Legoas R. (2022)
We gratefully acknowledge Rildo M. Moreira and staff of the Itatinga Research Station (ESALQ/USP) for authorization to conduct the experiment and Eder Araujo da Silva (http://www.floragroapoio.com.br) for technical support in the installation of the throughfall exclusion device and growth monitoring. We also thank Dr. Juan Sinforiano Delgado Rojas for support in installing, maintaining, and reading the automatic dendrometers. This research was funded by the Agropolis Foundation under reference ID1203-003 through the ?Investissements d'avenir? program (LabexAgro/ANR-10-LABX-0001-01), Conselho Nacional de Desenvolvimento Cient?fico e Tecnol?gico (CNPq) (444793/2014-3), and Fondo Nacional de Desarrollo Cient?fico, Tecnol?gico y de Innovaci?n Tecnologica (FONDECYT-CONCYTEC, Per?) (Award Number 239-2018). Roger Chambi- Legoas was supported by a scholarship from FONDECYT-CONCYTEC (Award Number 239-2018), and by a grant for yearly stays in Montpellier from the Centre de coop?ration internationale en recherche agronomique pour le d?veloppement (CIRAD) ?Action incitative-Soutien aux doctorants?.